(untitled) (Baghdad Science Journal, 2019)
In this study, Yogurt was dried and milled, then shaked with distilled water to remove the soluble materials, then again dried and milled. Batch experiments were carried out to remove hexavalent chromium from aqueous solutions. Different parameters were optimized such as amount of adsorbent, treatment time, pH and concentration of adsorbate. The concentrations of Cr6+ in solutions are determined by UV-Visible spectrophotometer. Maximum percentage removal of Cr6+ was 82% at pH 2. Two equilibrium adsorption isotherms mechanisms are tested Langmuir and Freundlich, the results showed that the isotherm obeyed to Freundlich isotherm. Kinetic models were applied to the adsorption of Cr6+ ions on the adsorbents, pseudo-first-order, the pseudo second-order respectively. Results showed that pseudo second-order kinetic model was applicable to the experimental data well. The thermodynamic parameters such as ΔGº, ΔHº and ΔSº were calculated. ∆H°, ∆S° and ΔGº for this study were negative indicating that the process is exothermic, while negative values of ΔGº indicate spontaneous process.